1965
DOI: 10.1083/jcb.25.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Biochemical Correlates of Cerebral Microsomes

Abstract: Microsomal fractions, both homogeneous in appearance and functionally operative, were isolated from a homogenate of rat cerebral cortex by fractionation in water. The preparations thus obtained contain the membranous elements of the endoplasmic reticulum, synaptic vesicles, and ribosomes. Esterase, ATPase, and glutamine synthetase were found to be present and fully functional in the microsomal fractions isolated in water. The contamination of the water-isolated microsomal fractions by mitochondria and lysosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1966
1966
1979
1979

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The differential susceptibility of glutamine synthetase to solubilization by 15 mMand 150 mM-NaC1 was noted previously (DE BALBIAN VERSTER et al, 1965). In the present studies, where a wide range of Na+ concentrations was tested, a polyphasic effect of this cation on the solubilization of the enzyme was noted, and the interesting observation made that Na+, when used between 10 and 60 mM, actually facilitates the retention of the enzyme in particulate form (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The differential susceptibility of glutamine synthetase to solubilization by 15 mMand 150 mM-NaC1 was noted previously (DE BALBIAN VERSTER et al, 1965). In the present studies, where a wide range of Na+ concentrations was tested, a polyphasic effect of this cation on the solubilization of the enzyme was noted, and the interesting observation made that Na+, when used between 10 and 60 mM, actually facilitates the retention of the enzyme in particulate form (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…These structures were not seen in the other subfractions in equally abundant numbers. That the presence of these structures does not reflect disaggregation or dissociation of native phospholipid-protein bonds which may have occurred as a result of the suspension of Fraction P, in 15 mM-NaC1 (to yield Fraction SP) is supported by the fact that identical structures could be readily seen in electron micrographs of the unfractionated pellet (Fraction P,) (DE BALBIAN VERSTER et al, 1965).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Glutamine synthetase (EC 6.3.1.2) is predicted by this hypothesis to be mainly glial in localisation, and glutaminase (EC 3.5.1.2) mainly neuronal (VAN DEN BERG & GARFINKEL, 1971;BALAZS et al, 1973). Histochemical studies of many brain areas and of retina strongly indicate a glial site for glutamine synthetase (BELL & NORENBURG, 1977;REIPE & NORENBURG, 1977) and previous subcellular fractionation studies (SELLINGER & DE BALBIAN VERSTER, 1962;DE BALBIAN VERSTER et al, 1965;SALGANICOFF & DE ROBERTIS, 1965) have indicated a microsomal or soluble fraction localisation and enrichment, which would be consistent with a glial localisation. The extent to which this enzyme is present in synaptosome fractions is obviously an important consideration in view of the concentration of glutaminase present.…”
mentioning
confidence: 85%